On the energy gap determination of organic optoelectronic materials: the case of porphyrin derivatives. Issue 3 (18th January 2022) - Aderne, Rian E.; Borges, Bruno Gabriel A. L.; Ávila, Harold C.; von Kieseritzky, Fredrik; Hellberg, Jonas; Koehler, Marlus; Cremona, Marco; Roman, Lucimara S.; Araujo, C. Moyses; Rocco, Maria Luiza M.; Marchiori, Cleber F. N.
Abstract : We attempt to reconcile experimental and theoretical methodologies for the determination of the energy gap, which is essential to properly characterize a series of key phenomena related to the applications of organic semiconductors. Abstract : The correct determination of the ionization potential (IP) and electron affinity (EA) as well as the energy gap is essential to properly characterize a series of key phenomena related to the applications of organic semiconductors. For example, energy offsets play an essential role in charge separation in organic photovoltaics. Yet there has been a lot of confusion involving the real physical meaning behind those quantities. Experimentally the energy gap can be measured by direct techniques such as UV-Vis absorption, or indirect techniques such as cyclic voltammetry (CV). Another spectroscopic method is the Reflection Electron Energy Loss Spectroscopy (REELS). Regarding data correlation, there is little consensus on how the REELS' energy gap can be interpreted in light of the energies obtained from other methodologies such as CV, UV-Vis, or photoemission. In addition, even data acquired using those traditional techniques has been misinterpreted or applied to derive conclusions beyond the limits imposed by the physics of the measurement. A similar situation also happens when different theoretical approaches are used to assess the energy gap or employed to explain outcomes from experiments. By using a set of porphyrin derivatives as model molecules, we discuss some key aspects of those important issues. The peculiar properties of these porphyrins demonstrate that even straightforward measurements or calculations performed in a group of very similar molecules need a careful interpretation of the outcomes. Differences up to 660 meV (∼190 meV) are found comparing REELS (electrochemical) measurements with UV-Vis energy gaps, for instance. From the theoretical point of view, a reasonable agreement with electrochemical measurements of the IP, EA, and the gap of the porphyrins is only obtained when the calculations involve the full thermodynamics of the redox processes. The purpose of this work is to shed light on the differences and similarities of those aforementioned characterization methods and provide some insight that might help one to develop a critical analysis of the different experimental and theoretical methodologies.